FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KUSTA DI WILAYAH KERJA PUSKESMAS MUARA SABAK TIMUR KABUPATEN TANJUNG JABUNG TIMUR - Willia Novita; Oka Lesmana; Pitoyo (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Background: Tanjung Jabung Timur Regency is ranked first in leprosy cases in 2019 with a total of 36 cases. In 2020 East Tanjung Jabung Regency recorded 14 new cases of leprosy. The Muara Sabak Timur Health Center is one of the health centers with the highest leprosy with a total of 25 cases until 2020. Objective: The purpose of this study was to determine the factors associated with the incidence of leprosy in the working area of the Muara Sabak Timur Health Center. Method: The design of this study uses a case control approach. The sample in the study usedÂ a 21 case group samples and 21 control group samples. Results: From the statistical test results contact history variable p-value 0.147 (OR 1.105), humidity variable p-value 0.334 (OR 1.875), ventilation area variable p-value 0.001 (OR 10.625), occupancy density variable p-value 0.000 (OR 15.438), clean water availability variable p-value 0.204 (OR 2.273), toilet ownership variable p-value 0.040 (OR 4.500), house floor variable p-value 0.707 (OR 1.328), and personal hygiene variable p-value 0.013 (OR 5,200). Conclusion: leprosy is highly contagious, especially in conditions of poor personal hygiene, crowded housing, and latrines and ventilation that do not meet health requirements. Keywords: Leprosy, personal hygiene, ventilation, humidity, residential density